Electrical Resistance, Stability and Mechanical Properties of PVC Composites Containing Graphite and Semiconductor for Sensor Technologies - Anıl Eker; Bircan Dindar (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study aimed to obtain a new flexible poly vinyl chloride (PVC) based composite with conductive or semiconductor properties. Additives were graphite and semiconductor zinc oxide (ZnO). A non-ionic surfactant was also firstly used to obtain a homogeneous composite. For the characterization of these new composites; humidification, electrostatic discharge (ESD), electrical resistance, thermal shock measurements, tensile test and morphological and microscopic (SEM) measurements were performed. For the light test, a “Solar simulator” with a 1000 W xenon lamp was used. The electrical resistance and tensile strength of the materials were measured at each test step. According to the data obtained, it was determined that the electrical resistance of the materials with high graphite content, without ZnO, is still stable, while the electrical resistance of the ZnO-doped materials decreases and their conductivity increases considerably in special stimuli such as light. P3G2Z (32% PVC, 60% Graphite, 8% ZnO) was greater than 3 MΩ, with a large change in conductivity after electrostatic discharge, reaching 1078.33 kΩ, with the largest difference observed. It was determined that the resistance of P2G3Z and P1G1Z composite materials under solar radiation decreased approximately 81 and 23 times, respectively. This event proves that the composites become light sensitive semiconductor. As a result, the electrical and mechanical data of flexible, sensitive, conductive and semiconductor new polymers by doping PVC with graphite and ZnO nanoparticles at different rates will make a great contribution to the sensor, actuator, management system control mechanisms, and the robots used in the automotive and defense industries.